2016
DOI: 10.1088/2053-1583/3/3/035014
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent transition metal dichalcogenide nanosheets through one-step liquid phase exfoliation

Abstract: Liquid phase exfoliation (LPE) from the bulk is an adequate method for the mass-production of thin nanosheets of transition metal dichalcogenides (TMDCs). However, making suspensions in which the extraordinary properties of mechanically exfoliated TMDCs are observable remains a challenge. We describe a mild LPE method to produce luminescent suspensions of MoS 2 and WS 2 in Nmethylpyrrolidone or isopropanol/water mixtures, without the need for a purification step. The key differences in our experimental procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 75 publications
4
40
0
Order By: Relevance
“…Finally, the most significant influence of NMP degradation is in its use as a solvent for photoluminescence spectroscopy of nanomaterials, despite the solvent itself exhibiting strong and broad photoluminescence. Such nanomaterials include conjugated polymers 17 , carbon nanotubes 18 , transition metal dichalcogenides 19 , 20 and black phosphorus 9 , 21 . For most of these materials, the photoluminescence is not in the same wavelength range as the NMP but the excitation wavelengths used could result in broad background luminescence from the solvent, although there is likely to be some quenching by the nanomaterial.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the most significant influence of NMP degradation is in its use as a solvent for photoluminescence spectroscopy of nanomaterials, despite the solvent itself exhibiting strong and broad photoluminescence. Such nanomaterials include conjugated polymers 17 , carbon nanotubes 18 , transition metal dichalcogenides 19 , 20 and black phosphorus 9 , 21 . For most of these materials, the photoluminescence is not in the same wavelength range as the NMP but the excitation wavelengths used could result in broad background luminescence from the solvent, although there is likely to be some quenching by the nanomaterial.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently described a “click” chemistry protocol for the covalent modification of colloidal semiconducting 2 H‐MoS 2 and WS 2 , obtained through liquid phase exfoliation (LPE) from the bulk . In our strategy, inspired by the many examples of thiol‐ene chemistry in polymer chemistry and biochemistry, we exploited the soft nucleophilicity of sulfur to make it react with the prototypical soft electrophile, maleimides (Figure ) …”
Section: Introductionmentioning
confidence: 89%
“…The exfoliation process in liquid leads to faster preparation method. However, the samples made by exfoliating in solution are extremely small, and it is difficult to control the layer number and size of the flakes 16 , 17 . Recently, it has been reported that the exfoliation of graphene in liquids by a nanosecond (NS)-pulse Nd:YAG laser is more effective for obtaining a large-sized and high-quality sample than the other liquid exfoliation methods 18 .…”
Section: Introductionmentioning
confidence: 99%